Transformasi Hukum Pidana Islam dalam Tata Hukum Indonesia - Munajat, Makhrus (Fakultas Syariah IAIN Purwokerto, 2019)
The formalization of Islamic criminal law in Indonesia is still and always debated in terms of its legal rules or the establishment of Islamic values, meaning that the substance is more important than the formal rules. Transformation of Islamic criminal law is a change that occurs in the determination of law, both concerning the type of crime (jarÄ«mah) or its sanctions due to time and social dynamics. The criminal act (jarÄ«mah) and its sanctions are interconnection between the principal law (al-aá¸¥kÄm al-aá¹£liyyah) which contains the prohibition and supporting law (al-aá¸¥kÄm al-muayyidah) which contains sanctions. The model of the transformation of Islamic criminal law in Indonesia is to make Islamic criminal law a law that can be accepted by Indonesian people, by not distinguishing ethnicity, adat (tradition), culture and religion. The objectivity of Islamic criminal law in Indonesia is used as the basis for the formation of national laws whose pluralistic communities are offered universal values so that they can be accepted by all citizens without questioning the origin of the values.